A First Approach to the Censoring Documentation of the Galician Drama (1942-1970) in the General Archive of the Administration - Fernández Poza, Óscar (Madrygal. Revista de Estudios Gallegos, 2020)
In this article we analyse some files of the Franco’s censorship that contain the requests for representation of the Galician drama generated in the period from 1942 to 1970 and kept in the General Administration Archive (Alcalá de Henares). In the first section, a historical approach to censorship is made; in the second, the internal functioning and organizational structure of censorship throughout these years is studied. Following these premises, the following sections analyse the files that were generated on Galician production and that have been kept in the AGA, both the requests for theatre representation in the period in question and the files on certain editions of the texts represented. From the documentation analysed, we can also deduce the evolutionary process of Galician dramaturgy in that chronology, from a theatre of traditional character to the new dramaturgies in Galician language, which were already close to those of contemporary European drama.
Keywords: Contemporany Galician Drama; General Archive of the Administration; Censorship